(αR,4R,4aR,6aS,7R,8S,10R,11S)-Methyl α-acetoxy-4-(3-furanyl)-10-hydroxy-4a,7,9,9-tetramethyl-2,13-dioxo-1,4,4a,5,6,6a,7,8,9,10,11,12-dodecahydro-7,11-methano-2H-cycloocta[f][2]benzopyran-8-acetate (6-O-acetylswietenolide) from the seeds ofSwietenia macrophylla - Goh, B.H.; Abdul Kadir, H.; Abdul Malek, S.N.; Ng, S.W. (International Union of Crystallography, 2010)
The molecule of O-acetylswietenolide, C29H36O9, isolated from the seeds of Swietenia macrophylla, features four six membered rings connected together in the shape of a bowl; one of the inner rings adopts a twisted chair conformation owing to the C C double bond. The furyl substitutent is connected to an outer ring, and it points away from the bowl cavity. The hydroxy group is connected to a carbonyl O atom of an adjacent molecule by an O—H O hydrogen bond, generating a chain running along the b axis.